Restaurant kids' meal beverage offerings before and after implementation of healthy default beverage policy statewide in California compared with citywide in Wilmington, Delaware. Issue 3 (12th March 2022) - Ritchie, Lorrene D; Lessard, Laura; Harpainter, Phoebe; Tsai, Marisa M; Woodward-Lopez, Gail; Tracy, Tara; Gosliner, Wendi; McCallops, Kathleen; Thompson, Isabel; Karpyn, Allison
Abstract: Objective: In 2019, California and Wilmington, Delaware' implemented policies requiring healthier default beverages with restaurant kids' meals. The current study assessed restaurant beverage offerings and manager perceptions. Design: Pre-post menu observations were conducted in California and Wilmington. Observations of cashiers/servers during orders were conducted pre-post implementation in California and post-implementation in Wilmington. Changes in California were compared using multilevel logistic regression and paired t tests. Post-implementation, managers were interviewed. Setting: Inside and drive-through ordering venues in a sample of quick-service restaurants in low-income California communities and all restaurants in Wilmington subject to the policy, the month before and 7–12 months after policy implementation. Participants: Restaurant observations (California n 110; Wilmington n 14); managers (California n 75; Wilmington n 15). Results: Pre-implementation, the most common kids' meal beverages on California menus were unflavoured milk and water (78·8 %, 52·0 %); in Wilmington, juice, milk and sugar-sweetened beverages were most common (81·8 %, 66·7 % and 46·2 %). Post-implementation, menus including only policy-consistent beverages significantly increased in California (9·7 % to 66·1 %, P < 0·0001), but remained constant in Wilmington (30·8 %). During orders, cashiers/servers offering only policy-consistent beverages significantly decreased post-implementation in California (5·0 % to 1·0 %, P = 0·002). Few managers (California 29·3 %; Wilmington 0 %) reported policy knowledge, although most expressed support. Most managers wanted additional information for customers and staff. Conclusions: While the proportion of menus offering only policy-consistent kids' meal default beverages increased in California, offerings did not change in Wilmington. In both jurisdictions, managers lacked policy knowledge, and few cashiers/servers offered only policy-consistent beverages. Additional efforts are needed to strengthen implementation of kids' meal beverage policies.